Materiality Thresholds in Accounting and Auditing Some UK Evidence - Chong, Gin (The International Journal of Accounting and Business Society, 2000)
This paper reports the telephone interviews with 12 auditors (Big 5 and non Big 5) and 14 non auditors on the materiality thresholds adopted by them or by their organisations. Non auditors include from ï¬nance directors, banker, lawyer, internal auditors, an academic, and technical directors of the Accounting Standards Board (ASB) and the Auditing Practices Board (APB) in the UK. This is in respond to the issuance of Statement of Auditing Standards (SAS) 220 on â€˜Materiality and the Audit= by the APB in 1995 whereby no materiality threshold was speciï¬cally mentioned. The ï¬ndings showed that 10% of net proï¬t before tax is the favourite threshold. This is close to recommendations from literature or due to inï¬‚uences by the literature themselves. A speciï¬c mathematical guideline could enhance harmonisation of reporting and interpretation of ï¬nancial results. key words: materiality, audit risk, auditors, true and fair view.